Bletilla striata Polysaccharides Improve Hemostatic, Antiinflammatory Efficacy, and Platelet Aggregation in Gingivitis Rat Model. (22nd December 2020) - Guo, Qing; Li, Bailei; Bao, Chunling; Li, Yixia; Cao, Yuling; Wang, Chunxiao; Wu, Wenhui
Abstract: In this study, the bioactivity of the Bletilla striata polysaccharides (BSPS) on platelet aggregation and anti‐inflammation is investigated. For this purpose, a physiological system in vitro is established to evaluate the hemostatic effect of BSPS by measuring the platelet aggregation (PAG) rate, cyclic adenosine monophosphate (cAMP), and thromboxane B2 (TXB2 ). A quantifiable inflammatory model of human gingival epithelial cells (HGECs) is established by inducing lipopolysaccharide (LPS) to evaluate the anti‐inflammatory effect of BSPS. An experimental gingivitis rat model in vivo is set up to further verify hemostatic and anti‐inflammatory efficacy of BSPS, which is comprehensively evaluated through the following five techniques: X‐ray morphological observation, hematoxylin‐eosin (HE) staining analysis, probe index (plaque index, gingival index, bleeding on probing) diagnostic evaluation, immunoglobulin (IgA, IgM, IgG), and cytokines. Interestingly, the changes of cytokines in vivo are in accordance with those in vitro. The positive effects of BSPS in hemostasis and anti‐inflammation are also confirmed by X‐ray observation and HE staining. The above results demonstrate that BSPS promotes platelet aggregation with an anti‐inflammatory effect, which suggests that the BSPS may be beneficial in the treatment of hemostasis and inflammatory diseases. Abstract : A novel platelet physiological model and an immune model of human gingival epithelial cells (HGECs) are used to investigate the anti‐inflammatory and hemostatic effects of Bletilla striata polysaccharide (BSPS), an animal gingivitis model in vivo to evaluate the effects of BSPS on experimental periodontitis. The results show that BSPS may be beneficial in the treatment of hemostasis and gingivitis.